The activity of a PI3K δ-sparing inhibitor, MEN1611, in non-small cell lung cancer cells with constitutive activation of the PI3K/AKT/mTOR pathway - Papoff, Giuliana; Presutti, Dario; Fustaino, Valentina; Parente, Andrea; Calandriello, Clelia; Alemà, Stefano; Scavizzi, Ferdinando; Raspa, Marcello; Merlino, Giuseppe; Salerno, Massimiliano; Bigioni, Mario; Binaschi, Monica; et al. (Frontiers in Oncology, 2023)
Lung cancer remains the leading cause of cancer death worldwide. Targeted therapies with Tyrosine kinase inhibitors (Tki) result in improvement in survival for Non-Small Cell Lung Cancer (NSCLC) with activating mutations of the Epidermal growth factor receptor (EGFR). Unfortunately, most patients who initially respond to EGFR-Tki ultimately develop resistance to therapy, resulting in cancer progression and relapse. Combination therapy is today a common strategy for the treatment of tumors to increase the success rate, improve outcome and survival of patients and avoid selection of resistant cancer cells through the activation of compensatory pathways. In NSCLC, the phosphoinositide-3-kinase/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway has been heavily implicated in both tumorigenesis and the progression of disease. In this study, we investigated the efficacy of a PI3K δ-sparing inhibitor, MEN1611, in models of NSCLC sensitive and resistant to the EGFR inhibitors (erlotinib and gefitinib) with a wild type PIK3CA gene. Functional, biochemical and immunohistochemistry studies were performed. We demonstrate a good efficacy of MEN1611, in NSCLC devoid of PIK3CA gene mutations, but with a constitutive activation of the PI3K/AKT pathway and its synergic effect with gefitinib both in vitro and in vivo. Overall, this preclinical study indicates that the inhibitor could be a candidate for the treatment of NSCLC with a resistant erlotinib/gefitinib phenotype and constitutive activation of the PI3K/AKT pathway, a phenotype mimicked by our model system.